(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses the origin and development of the semantics as an independent linguistic field conducted by foreign and Uzbek scholars. It also deals with general analysis of linguistic works related to the semantics which studies the framework of the development of meaning, fundamental studies, broad study of semasiology in a certain languages. Furthermore, it is analyzed the views about semantics and semasiology as a linguistic term.